Investigation of the effect of the dual orexin receptor antagonist almorexant on ophthalmological, spermatogenic, and hormonal variables in healthy male subjects - Dingemanse, Jasper; Charef, Pascal; Black, Jed; Gouws, Chris (Biomedicine & pharmacotherapy, 2021)
•The dual orexin receptor antagonist almorexant was administered once daily to healthy male subjects for 4 weeks.•A battery of ophthalmological, spermatogenetic, and hormone variables was assessed.•No clinically relevant effects were detected in spite of some findings in toxicology studies in rats and dogs. The aim of this single-center, double-blind study was to investigate the effect of a 4-week once daily administration of 200 mg almorexant on tear film break-up time, spermatogenesis, hormone levels, and pancreatic elastase in stool in healthy male subjects. Almorexant 200 mg or matching placebo was administered in the evening for 4 weeks once daily to 56 healthy male subjects. Changes in ophthalmological variables, sperm composition, hormone levels, and pancreatic elastase levels in stool were evaluated periodically up to 8 weeks after discontinuation of drug administration. Blood samples for pharmacokinetic measurements were taken after 4 weeks to confirm compliance to study drug intake. The results of this study revealed no treatment effects of almorexant, neither on tear film break-up time nor on other ophthalmological variables investigated during this study. Furthermore, spermatogenesis, hormones of the hypothalamic-pituitary-adrenal and –gonadal axes, and endocrine pancreatic secretion were shown to be not affected by a 4-week once daily administration of almorexant. Almorexant was well tolerated and had no effect on the spectrum of pharmacodynamic variables assessed. Ophthalmology and testicular findings detected in preclinical studies were not observed in this clinical study. Therefore, these preclinical findings appear not to be relevant for humans and do not prevent from conducting larger clinical trials with either healthy subjects or patients.